THE USE OF ICT IN THE PROFESSIONAL DEVELOPMENT OF TECHNICAL AND VOCATIONAL EDUCATION INSTRUCTORS IN SUDAN AND EGYPT - Hassan A. El-Sabagh; Hashim A. E. Ahmed (Sanata Dharma University Yogyakarta, 2020)
This paper provides an initial attempt to study and investigate the interactive relationship between vocational and technical education instructors and using information and communications technology (ICT) and its impact of the professionalism of their work. The paper compares the ICTs usage in vocational and technical instructors in Sudan and Egypt as important countries in Africa. This paper explores two contexts ''environments'' that initially appeared a little bit different. It presents results of a survey administered to several instructors in Sudan (95) and in Egypt (120) which show that, excepting a few tasks, vocational instructors in both countries. Instructors from both countries responded similarly about (a) where they learned about ICT (for example, computers and Internet) and (b) the usefulness of ICT for technical and vocational centers in both countries. They also indicated feeling minimal concern when using technology. Furthermore, differences were in evidence in both countries where desire to use technology was concerned. Overall, Sudanese instructors showed a greater features and range in their choices when given the option to traditional teaching methods preferable than technology use to complete various tasks, whereas Egyptian clarified more attitudes toward technology compared to other context.